Hubungan Dukungan Keluarga dengan Tingkat Depresi Pasien HIV/AIDS - Wiwin Martiningsih; Fransnedo Dhiky Kurnia C; Sri Winarni (Journal of Ners and Midwifery, 2015)
AIDS is a collection of specific clinical conditions that are the end result of infection by HIV. This raises the issue of psychiatric illness, namely depression. Depression is what causes the quality of life of patients with HIV / AIDS become less well. To handle this condition needed social support from family. The purposes of this study were to identify family support and levels of depression, and analyzed the correlation between the two variables. This study used correlative as research design. Purposive sampling is used to get samples. The total of study subjects were 34 people who registered in the registration book in January to October 2013, and visited hospitals in Cendana Polyclinic Ngudi Waluyo Hospital Wlingi and included the inclusion criteria. Family support data was obtained base of questionnaire and depression levels was obtained by The Zung Self-Rating Depression Scale questionnaire. Data showed that 94,1% respondents got family support well andÂ  97,1% respondent have not depression symptoms. The correlation between family support with depression levels analyzed using Spearman's rho test with a significance level of p = 0.000, showed that the correlation between family support for the patient's level of depression of HIV / AIDS significantly. From this study can be concluded that the respondents with good family support did not experience symptoms of depression. Families need to provide support for its members who suffer from HIV / AIDS in order to prevent depression.